How is the United States’s international HIV prevention programme evolving? - Evain, Christine (Advances in Social Sciences Research Journal, 2018)
The President’s Emergency Plan For AIDS Relief (PEPFAR) is a 1998 United States governmental initiative to prevent the spread of AIDS, primarily in Africa. The PEPFAR program has provided antiretroviral treatment to over 11 million HIV-infected people in Africa and it has been called the largest health initiative ever initiated by one country to address a disease, with a budget exceeding 70 billion since its creation. While PEPFAR has been praised for having saved millions of lives, diminishing media attention to AIDS as well as potential policy changes are likely to negatively impact the progress of the organization in the future. Thus a number of questions arise: How has PEPFAR’s policy been driven and assessed so far? What are the key factors which have led to PEPFAR’s success? How does it measure its own efficiency? How does PEPFAR compare to other international organizations? What are its links with local organizations? How does it relate to its partners? The aim of this paper is to consider these important questions and to map out the shifting balance of HIV prevention in the next decade. This study is based on the institutional documentation, press articles as well as on a series of interviews conducted with local members of HIV/AIDS Disease Control and Prevention programmes in Africa.